The Role of Dayah in Instituting Religious Tolerance Behaviors in Students of Aceh Singkil - Desriadi, Desriadi; Ananda, Rusydi; Arsyad, Junaidi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research is motivated by the problematic interfaith relations in Aceh Singkil Regency, marked by horizontal conflicts in 1979 and 2015, as well as the strategic position of dayah as traditional Islamic educational institutions in a multicultural society with religious diversity. This study aims to analyze the role of dayah in Instituting religious tolerance among students in Aceh Singkil. This research uses a qualitative method with a case study approach in three Three Dayah in Aceh Singkil. This study concludes that dayah has a strategic role in shaping religious tolerance behavior through moral education, Islamic values, and inclusive socio-religious practices. The implementation of these findings can be achieved by strengthening teacher capacity, developing an integrated curriculum, organizing student exchange programs, revitalizing local wisdom, enhancing technology-based learning media, and conducting regular monitoring and evaluation. The research findings are implemented through strengthening teacher capacity to teach the values ​​of tolerance in an integrated manner, developing a curriculum that integrates Islamic teachings with inclusive religious practices, and implementing a cross-community student exchange program. These efforts are reinforced by revitalizing local wisdom that instills a spirit of togetherness, utilizing digital media to disseminate content on tolerance and develop critical literacy in students, and conducting regular monitoring and evaluation to ensure the effectiveness and sustainability of all programs.